Pengaruh Penggunaan Obat Tradisional Terhadap Kualitas Hidup Pasien Dengan Penyakit Kronis Di Desa Berjo - Ningrum, Andriani Noerlita; Setyorini, Catur; Rokhmatun, Puji Nur; Lieskusumastuti, Anita Dewi (Yayasan Jompa Research and Development, 2025)
Objective: This study aims to evaluate the effect of traditional medicine use on the quality of life of patients with chronic diseases in Berjo Village, Kemuning Subdistrict, Karanganyar Regency.Methods: This research employed an analytical observational design with a cross-sectional approach. The study population included patients aged 18–65 years with at least one chronic disease diagnosis (hypertension, diabetes mellitus, or heart disease) who had been using traditional medicine for ≥3 months. A total of 28 respondents were selected using purposive sampling. The independent variables were the timing and duration of traditional medicine use, while the dependent variable was quality of life, measured using the Indonesian version of the SF-36 questionnaire. Data analysis included descriptive statistics, Kolmogorov-Smirnov test, Spearman correlation, and Chi-Square test at a 5% significance level.Results: Respondents who used traditional medicine concurrently with illness had 22 times higher odds of having a good quality of life (p=0.001; OR=22), and those who used it for more than 4 weeks had 48 times higher odds (p=0.000; OR=48).Conclusion: The timing and duration of traditional medicine use are significantly associated with patients’ quality of life, with family support playing a crucial role in treatment decision-making.